PRIORITY MANAGEMENT OF CORAL REEF ECOSYSTEMS IN POMBO ISLAND NATURE TOURISM PARK, CENTRAL MALUKU REGENCY: PRIORITAS PENGELOLAAN EKOSISTEM TERUMBU KARANG DI TAMAN WISATA ALAM PULAU POMBO, KABUPATEN MALUKU TENGAH - Samsul Bahri Rumasoreng; Fredinan Yulianda; Gatot Yulianto (Fakultas Perikanan dan Ilmu Kelautan, IPB University, 2026)
The coral reef ecosystem in the Pombo Island Nature Tourism Park area has experienced a decline in quality due to environmentally damaging fishing practices, thereby affecting coral reef productivity. This study aims to identify the actual condition of the coral reef ecosystem by analyzing water quality, the level of live coral cover, and the reef fish species abundance to formulate a main-priority management strategy. Water quality parameters were measured directly, while coral reefs were measured through diving using scuba gear. Coral condition evaluation was carried out using the point intercept transect method, while reef fish abundance was calculated using the underwater visual census technique. Determination of priority strategies for coral reef ecosystem management used the analytic network process approach. The results showed that water quality was considered good to support coral reef ecology. The average coral cover was 47.75% (fair category), with variations between blocks: utilization (24%, poor), rehabilitation (35%, fair), marine protection (57%, good), and traditional (42%, fair). Forty-nine reef fish species from 16 families were found with an abundance of 2,545 individuals per 1,500 m² of observation area, including major, target, and indicator fish, and the species abundance was categorized as high. Coral reef ecosystem restoration can be prioritized through community-based coral transplantation to enhance the effectiveness of both restoration efforts and environmental education.